1992
DOI: 10.1021/ma00045a030
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic-liquid crystal phase equilibrium in semiflexible polymer solutions: effects of molecular weight and ionic strength in polyelectrolyte solutions

Abstract: The isotropic-liquid crystal (cholesteric) phase boundary concentrations for aqueous solutions of xanthan, an ionic double-helical polysaccharide, were determined as functions of the molecular weight of xanthan and the added sodium chloride concentration. The phase boundary concentrations increased sharply with decreasing molecular weight at low molecular weights, as in the case of neutral stiff polymer solutions, and depended strongly on the added salt concentration. The latter dependence demonstrates the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 10 publications
(16 reference statements)
3
52
0
Order By: Relevance
“…For samples with narrow molecular weight distribution (MWD) both c i and c a approach asymptotic values as the molecular weight of the xanthan becomes great enough to make the mean contour length L of the polymer equal to about one Kuhn length, which for wormlike chains is 2q. 16 The concentrations c i and c a are in the range of 0.1 g cm -3 at high C s and comparable to those characterizing the lyotropic phase diagrams of neutral rigid polymers. 17 As C s is reduced, both c i and c a decrease sigmoidally as electrostatic effects become prominent in the intermolecular potential.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…For samples with narrow molecular weight distribution (MWD) both c i and c a approach asymptotic values as the molecular weight of the xanthan becomes great enough to make the mean contour length L of the polymer equal to about one Kuhn length, which for wormlike chains is 2q. 16 The concentrations c i and c a are in the range of 0.1 g cm -3 at high C s and comparable to those characterizing the lyotropic phase diagrams of neutral rigid polymers. 17 As C s is reduced, both c i and c a decrease sigmoidally as electrostatic effects become prominent in the intermolecular potential.…”
Section: Introductionmentioning
confidence: 65%
“…Using a sample with molecular weight 2.35 × 10 5 , Milas and Rinaudo were the first to measure the steady shear viscosity of xanthan in 0.1 M aqueous NaCl into the biphasic and completely anisotropic domains, where they observed behavior similar to that of rodlike synthetic polymers. 14 Allain et al 67 carried out a similar, more extensive, 16 ). Phase separation results for X2F2 and X13F3 at 23°C (larger symbols) from Figure 3; the vertical dashed lines indicate the corresponding molecular weights of these samples.…”
Section: Introductionmentioning
confidence: 99%
“…The axis ratio (L/d) and ionic strength are critical parameters in the degree of shear induced order, as well as for the relaxation behavior after shear ceases. [59,[82][83][84][85][86] Complementary to these investigations, Orts et al, [82] using SANS experiments, demonstrated the anisotropic shear ordering of cellulose microcrystals when studying black spruce bleached kraft pulp. Under shear these cellulose microcrystals showed an anisotropic alignment where the distance between the rods scales with C À1/2 at high concentrations.…”
Section: Optical and Orientation Propertiesmentioning
confidence: 91%
“…[91] These forces are governed by the axis ratio, the polydispersity in particle length, the surface charge density, the ionic strength, and the nature of the counter ions present in the whisker suspension. [59,[83][84][85]91] On the other hand, for perfect neutral rods with length L and diameter d, the critical concentration to display the ordered phase is only dependent on the axis ratio L/d, according to Onsager's theory. [92] However, for the charged rods, the electrostatic interactions play a key role in the phase separation.…”
Section: Polyelectrolytic Naturementioning
confidence: 99%
“…The charge density o and the total salt concentration n together with geometrical parameters of the chains are supposed to be arbitrary parameters. The validity of our approach is based on the conditions (6), (9), (ll), (12), (13), (15). Among them the conditions (9), (ll), (15) are not very crucial: if they are not fulfilled, one should make the renormalizations (8) for o, n + nClj for n and (14) for persistent length 1.…”
Section: Lomentioning
confidence: 99%